(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This paper explores ways in which virtual learning can facilitate improved access to information, promote openness, and encourage flexibility in an open and distance learning university. It reports on experiences and perceptions of students at an open and distance learning university, who study through virtual learning. The study considered two groups studying the same programme, under different conditions. One group had facilitators during face-to-face sessions while the other used a virtual classroom, using smartboard technology. The sample consisted of thirty-two (32) students from Botswana Open University (BOU). An exploratory mixed methods approach was used. Students were purposively sampled. A questionnaire was administered to establish the extent to which virtual learning delivery mode provided improved access, openness and flexibility. For data analysis, themes of students’ responses were identified and tallied according to the different issues and trends that emerged. The findings suggest that students view virtual learning not as significantly different from the face-to-face session in terms of quality of content. However, students reported low levels of satisfaction regarding interactivity and poor video quality.